Islamic Education Teachers' Strategies in Fostering the Morals of Vocational High School Students - Syafruddin (Jurnal Pengembangan Profesi Guru dan Dosen, 2024)
The process of guidance and moral development for students is a momentum to overcome all kinds of student actions that lead to behavior that is not in accordance with norms, so that guidance and counseling provide solutions and alternatives for all kinds of problems faced by students. In order to develop their morals, Islamic Religious Education teachers need to use special strategies so that they are expected to have a positive impact on improving their religious beliefs and developing their morals. This research aims to: (1) examine in depth the strategies used by Islamic Religious Education (PAI) teachers in developing students' morals at SMK in Aceh, (2) analyzing the moral development patterns implemented, (3) identifying supporting factors and obstacles in the process of moral development. This research uses a descriptive qualitative approach, with data collection techniques through observation, interviews and documentation. The results of this research show that PAI teachers at SMK in Aceh use various strategies to develop students' morals, including example, habituation, advice, punishment and training. The moral development pattern implemented at SMK Aceh includes various routine activities such as reading prayers and the Koran before starting learning and special programs such as recitations and lectures once a week. Supporting factors in moral development at SMK in Aceh include commitment and good cooperation between teachers, parents and students, as well as a school environment that supports moral development through various positive activities. Apart from that, support from the school in providing programs that support moral development is also an important factor. Several inhibiting factors include the lack of supporting facilities and infrastructure such as special rooms for religious activities and the negative influence of the environment outside the school which can influence student behavior.